Experimental evaluation of RCC beam under elevated temperature and its GFRP retrofitting - Kagale, Sujan V.; Patil, P. S. (Journal of Structural Engineering, 2025)
This paper present an experimental evaluation of effect of elevated temperature on R.C.C beam and its retrofitting with the help of glass fiber reinforced polymer sheet. The GFRP sheet was banded to beam externally with the help of epoxy resin. In this experimental work total sixteen beams were casted and cured for twenty eight days. After the curing period two control beams are tested under room temperature and the remaining beams subjected to heating in the electrical furnace at various temperature interval. For each temperature interval four beams heated in the furnace and after that these beams are cooled under natural environmental condition. Out of four beams which is heated at one particular temperature two beams subjected to direct loading and the other two subjected to loading after their retrofitting. The same procedure is adopted for each temperature interval and a result of experiment is noted down. From the result it is conclude that the strength of beam decrease suddenly after 600°C and physical properties get changes. The result indicates that the strength of retrofitted beams gets increased as compared to control beams at various temperature intervals.